Transforming Physics Learning Media in Indonesian Senior High Schools: A Decade of Systematic Innovation Review (2014–2024) - Silvina Anandita, Aulia; Negoro, Ridho Adi; Rahmawati, Lusy (Kasuari: Physics Education Journal (KPEJ), 2025)
Innovations in instructional media play a pivotal role in enhancing student engagement and conceptual understanding in secondary-level physics education. Over the past decade, Indonesian schools have witnessed a marked transition from conventional tools to digital technologies and environment-based approaches. This study systematically reviews the development and characteristics of physics learning media employed in Indonesian senior high schools from 2014 to 2024. Utilizing a systematic literature review method, it synthesizes findings from 24 articles published in nationally accredited journals and relevant scholarly sources. The review reveals a growing adoption of digital media—such as interactive simulations, augmented reality (AR), and learning management systems (LMS)—while conventional and context-based media remain pedagogically relevant in specific settings. The findings underscore the importance of integrating adaptive instructional media with local contextualization and infrastructure support to ensure sustainable innovation in physics education at the secondary level.